Cyberabad, modèle de ville post-moderne ? - Eric Leclerc (EchoGéo)
The emergence on the outskirts of major Indian cities of real boomtown whose landscapes break with the rest of the former urban fabric, questions observers. Some see the emergence of a new urban model, described as postmodern, for the contrasts and social fragmentation that it generates. A rereading of the transposition of the concept of modernity in India casts doubt on the reality of an interpretation by the gap and the utility of the use of post-modernity to interpret these changes. From the example of Cyberabad on the outskirts of the capital of Andhra Pradesh, Hyderabad, one can observe how the described boundaries are crossed and the appearance of places where hybridity of urban society is realized.